The principle of I'tibar Maalat in issuing the fatwas of muslim minorities - Muhammad Shahrul Ifwat, Ishak; Nur Syahirah, Mohammad Nasir; Abdul Manan, Ismail (2019)
Imam Al-Shatibi has come up with the idea of considering maalat in order to deal with Sharia rules, by considering their consequences when these rules come to be implemented in reality. It is understood that mujtahid sometimes could not apply rules as their origin as revealed, to avoid from removing the maslahah (wisdom) that aimed by God through those rules. Therefore, this research attempts to explain the concept of the principle of considering maalat as well as its parameters in issuing fatwa of Muslim minorities. As known, some circumstances of Muslim minorities have their own characteristics which would be different than Muslim majorities in various aspects of life. Therefore, it is required for Mufti to consider maalat in issuing a fatwa, for the sake of maslahah of Muslim. Based on two methods: inductive and deductive, the findings are: considering maalat must be applied under parameters of ijtihad (an effort to issue the ruling from its sources); the rule must be understood in terms of its illah (legal reasoning) and its wisdom; the consequences must be real or strongly expected; considering priorities between maslahah; and do not abolish the original rule.